Sierra Leone 2021 Economic Update : Welfare and Poverty Effects of the COVID-19 Pandemic - World Bank (World Bank, Washington, DC, 2021)
The global economy is projected to grow 6 percent in 2021, stronger than had previously been expected, reflecting fiscal support in advanced economies, especially the US, and faster rollout of vaccines than anticipated. However, amid COVID-related uncertainty, recoveries are varying within as well as between countries. Growth is projected to vary substantially depending on the policy space available, and how much a country relies on tourism and commodity exports. While advanced economies as a group are now projected to grow by 5.1 percent in 2021, growth in Sub-Saharan Africa (SSA) will rebound by only 3.4 percent. The immediate and medium-term policy priorities should focus on strengthening the response to the COVID-19 pandemic by rolling out a strong vaccination program and implementing broad-based macroeconomic reforms to support a quick economic recovery. First, to prevent a severe second wave from disruption economic recovery over the medium-term, the authorities should develop and implement a robust vaccination program that targets inoculation of population ‘at risk’ (health workers, persons aged 70 years and those with comorbidities) and all adults. Sierra Leone’s access to vaccines could depend on its strategic relationship with key development partners and vaccine-producing nations. The country should strengthen alliances with development partners and support multilateral-led approaches by the African Union to increase its access to vaccines. Second, addressing existing macroeconomic weaknesses and implementing reforms to mitigate the existing risks to medium-term recovery will be critical for a sustained inclusive economic recovery that supports poverty reduction. Fiscal Policy can also be useful in ensuring that the economic recovery is pro-poor and inclusive. For the recovery to be pro-poor and pro-welfare, fiscal policy should balance the risks from growing debt with those from premature consolidation. Given the limited fiscal space, policy support should focus on expenditure reprioritization toward social sectors to ensure wider access to basic public services, especially vaccinations. This reprioritization effort should be grounded on credible medium-term fiscal frameworks. Both pre-distributive (policies that affect the distribution of market income) and redistributive (after-market) are needed to tackle poverty and inequality over the recovery period. Predistributive policies include measures to enhance access to basic services. Redistributive policies include tax and transfer policies designed to reallocate income from the top to the bottom of the income scale.